F4. THE EFFECT OF ANTIPSYCHOTICS IN THE TREATMENT OF SCHIZOPHRENIA ON LIPID PARAMETERS: A SYSTEMATIC REVIEW AND META-ANALYSIS OF PLACEBO-CONTROLLED TRIALS - Hagi, Katsuhiko (Schizophr Bull, 2019)
BACKGROUND: Antipsychotics have serious metabolic adverse effects on lipid parameters. However, the comparative influence of antipsychotics on lipid parameter levels has not been comprehensively evaluated. We conducted a systematic review and meta-analysis to evaluate the adverse effects of antipsychotics on changes in total cholesterol, LDL cholesterol, and triglyceride levels. METHODS: A systematic literature searches of the PubMed, EMBASE, Scopus, and Cochrane databases (last search Oct. 2018) was conducted to identify studies that reported randomized placebo-controlled trials (RCTs) comparing changes in total cholesterol, LDL cholesterol, and triglyceride levels between patients receiving antipsychotic or a placebo for the treatment of schizophrenia or related disorders. The primary outcome of interest was mean changes from baseline in those lipid parameter levels. RESULTS: We included 25, 22, and 27 studies reporting changes in total cholesterol, LDL cholesterol, and triglyceride levels, respectively. Of the 9 antipsychotics, olanzapine, quetiapine, and risperidone were associated with significantly increased total cholesterol compared to a placebo (standardized mean difference (SMD) = 0.43, 95% confidence interval (CI) = 0.28 to 0.57, p < 0.001; SMD = 0.41, 95% CI = 0.29 to 0.54, p < 0.001; SMD = 0.20, 95% CI = 0.05 to 0.36, p = 0.011, respectively). Of the 8 antipsychotics, olanzapine and quetiapine were associated with significantly increased, and cariprazine was associated with significantly decreased LDL cholesterol compared to a placebo (SMD=0.32, 95% CI= 0.18 to 0.47, p<0.001; SMD=0.26, 95% CI=0.11 to 0.40, p=0.001; SMD = -0.16, 95% CI = -0.27 to -0.06, p=0.003, respectively). Of the 10 antipsychotics, olanzapine, quetiapine, and risperidone were associated with significantly increased triglyceride compared to a placebo (SMD = 0.42, 95% CI = 0.31 to 0.52, p < 0.001; SMD = 0.32, 95% CI = 0.20 to 0.44, p < 0.001; SMD = 0.17, 95% CI = 0.02 to 0.33, p = 0.029, respectively). DISCUSSION: Olanzapine, quetiapine and risperidone were associated with significantly greater change in lipid parameter levels than placebo treatment. The comparative influence of lipid parameter-related side effects may help clinicians tailor the choice of antipsychotics to meet the needs of individual patients.